Synthesis, Characterization, and Toxicity Studies on Three Amino Acid Schiff-Base Ligands and Their Potential Binding Sites to Ni(II) ion: Comparison with Computational Density Functional Theory (DFT) Studies - Yang, Liang; Du, Huai Ming; Sheets, Tara; Karime, Coulibaly Wacothon; McLoud, Josh Daniel; Stewart, Tobias; Titah, James Tembei; Fan, Hua Jun (European Journal of Applied Sciences, 2023)
Three Schiff-base ligands derived from amino serine, leucine and phenylalanine and salicylaldehyde, benzaldehyde and N-4-dimethylaminobenzaldehyde respectively were successfully synthesized and characterized. In addition, three Ni(II) complexes were synthesized in situ and characterized with the above Schiff-bases. The structures of these complexes were investigated experimentally and computationally using density functional theory (DFT) technique to determine the potential binding environment with the Ni(II) center. Simulation of different models of the complexes were fully optimized using computational DFT B3LYP technique and the results revealed that models 4a, 5a, and 6a correspond to complexes-I, II, & III respectively. All the three complexes adopt a stable square planar geometry around the Ni(II) center. The complexes were characterized using melting point/decomposition temperatures, solubility test, FT-IR and UV-visible spectroscopy and the results compared with calculated results. The melting points/decomposition temperatures of all the complexes were different from the melting points of the starting amino acids used in their syntheses and the complexes were found to be soluble in water and other polar solvents. Experimental FT-IR and UV-Visible results agree with calculated results within accepted levels (5-10 %). The experimental imine ν(C=N) stretching frequencies of all the three complexes agrees well with the calculated results while the rest of the stretching frequencies show some discrepancies. Furthermore, the UV-Visible spectra the three electronic transitions HOMO-6àLUMO, HOMO-2àLUMO+1, and HOMOàLUMO+1 for complex-I, two transitions HOMO-2àLUMO+1 and HOMO-1àLUMO for complex-II, and two transitions HOMO-7àLUMO and HOMOàLUMO+1 for complex-III. The complexes were non-toxic towards prokaryotic gram positive (Staphylococcus aureus, Staphylococcus epidermis, Streptococcus mutants) and gram negative (Aquaspirillum serpens Escherichia coli) bacterial and eukaryotic (Saccharomyces cerevisiae) bacterial.